A Study of Relationship Between the Functions of Thinking Styles and Academic Achievement Among Student of Faculties of Technical and Engineering in the University of Tehran - Mehdi Abolghasemi kajafabadi; Farhad Nazarifar; Hadi Kamali; Tooraj Hoseini hafashjani (آموزش مهندسی ایران, 2010)
This study aims to investigate the relationship between the function of thinking styles and academic achievement among students of Faculties of Technical and Engineering in the University of Tehran. Analysis also considered sexual difference in the functions of thinking styles. 146 persons were selected using stratified sampling method(including 74 men and 72 women). Sternberg and Wagner's thinking styles questionnaire and self- reported form of academic achievement were used to collect data. Person correlation, multiple regression and T test were used to analysis the data. Findings showed that there is a positive and significant correlation between thinking styles and academic achievement. It was also found that executive thinking styles can only explain academic achievement and that women and men are significantly higher, at executive thinking styles and judicial thinking styles, respectively.